PERANAN MAJLIS AMANAH RAKYAT DALAM PENUBUHAN DAN PERKEMBANGAN INSTITUT TEKNOLOGI MARA, 1966-1976 - Abdul Kadir, Zarina Begam binti; Mohd Rus, Ahmad Kamal Arifin bin (SEJARAH: Journal of the Department of History, 2017)
This article attempts to analyse the role of Majlis Amanah Rakyat (MARA) in the development of Institut Teknologi Mara (ITM), within its 10 years of establishment. The basis of MARA’s role was primarily initiated by the Malay scholars and politicians, due to their concern on Malay socio economic disparity after Independence. Hence, by the consensus of the Bumiputera Economics Congress in 1965, MARA has been established as the outcome of the restructuring of RIDA. In addition, through the MARA’s initiative, Dewan Latihan RIDA has been upgraded to ITM in 1967. Also, by its further efforts, the Bumiputera’s level of education has been improved and enhanced its economic values. Further, the introduction of the professional courses in that institution, has aimed for the sustainability of the ITM’s graduates to compete in the higher income earnings market. Within 10 years of its establishment, it has shown a remarkable progress. However, due to the ineffectiveness administration of the Students’ Affair to curb the 1976 students’ riot, the ITM administration has been transferred to the Ministry of Education of Malaysia.